ENERAPAN FORWARD CHAINING SEBAGAI IDENTIFIKASI DAMPAK NEGATIF KECANDUAN GAME ONLINE PADA KESEHATAN MENTAL DAN PERILAKU REMAJA - Sadza Wardani, Farisa; Lestanti, Sri; Chulkamdi, M. Taofik (Antivirus : Jurnal Ilmiah Teknik Informatika, 2022)
The development of increasingly sophisticated technology provides changes in the form of human activity, one of which is the type of game. With the advent of audio-visual games that can be accessed via the internet. Known by the name of online games. Playing online games with a high level of intensity can have a positive or negative impact. The risk of dependence that can arise from online game addiction can cause mental health problems and behavioral changes that can occur in adolescents. So it is necessary to identify based on the habit of playing online games in adolescents. From solving these problems, an expert system was created to see whether the habits of playing online games by teenagers affected their mental health and behavior. The forward chaining method is used for the inference engine on the expert system to process data from interviews with experts in the field of psychology, there are 17 symptoms in the form of addiction disorders based on aspects of health, psychological, academic, social and financial aspects. Based on the results of the analysis, expert system testing was carried out using verification and validation tests by testing the rules compiled based on the forward chaining method as many as 39 data, the verification test produced results that matched the rules compiled with the results from expert experts and the system validation test resulted in a percentage of 94 %. So based on the research that has been done, the forward chaining method can be used in determining the diagnosis of the negative impact of online game addiction on mental health and adolescent behavior.